Degrees of Belief - Huber, Franz; Schmidt-Petri, Christoph; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2009)
The idea that belief comes in degrees is based on the observation that we are more certain of some things than of others. Various theories try to give accounts of how measures of this confidence do or ought to behave, both as far as the internal mental consistency of the agent as well as his betting, or other, behaviour is concerned. This anthology is the first book to give a balanced overview of these theories. It also explicitly relates these debates to more traditional concerns of the philosophy of language and mind, and epistemic logic, namely how belief simpliciter does or ought to behave. The paradigmatic theory, probabilism (which holds that degrees of belief ought to satisfy the axioms of probability theory) is given most attention, but competing theories, such as Dempster-Shafer theory, possibility theory, and AGM belief revision theory are also considered. Each of these approaches is represented by one of its major proponents. The papers are specifically written to target advanced undergraduate students with a background in formal methods and beginning graduate students, but they will also serve as first point of reference for academics new to the area. "This is a fascinating collection that brings together issues in traditional and formal epistemology, and succeeds in posing new challenges for both." Bas C. van Fraassen, San Francisco State University "This is a splendid collection of essays on degrees of belief. [...] the essays are so clear and general that the book also provides an excellent overview of the field for the non-expert." Frank Arntzenius, University College, Oxford University "Anyone interested in formal epistemology, or in the implications of formal epistemology for philosophy in general, should read this collection." Brian Weatherson, Rutgers University .
Belief and Degrees of Belief -- Belief and Degrees of Belief -- Plain Belief and Degrees of Belief -- Beliefs, Degrees of Belief, and the Lockean Thesis -- The Lockean Thesis and the Logic of Belief -- Partial Belief and Flat-Out Belief -- What Laws Should Degrees of Belief Obey? -- Epistemic Probability and Coherent Degrees of Belief -- Non-Additive Degrees of Belief -- Accepted Beliefs, Revision and Bipolarity in the Possibilistic Framework -- A Survey of Ranking Theory -- Arguments For$1 (BOr Against$1 (BProbabilism? -- Diachronic Coherence and Radical Probabilism -- Accuracy and Coherence: Prospects for an Alethic Epistemology of Partial Belief -- Logical Approaches -- Degrees All the Way Down: Beliefs, Non-Beliefs and Disbeliefs -- Levels of Belief in Nonmonotonic Reasoning.s
Keywords: Epistemology; Philosophy and science; Probabilities; Artificial intelligence; Logic; Mathematical statistics; Epistemology; Philosophy of Science; Probability Theory and Stochastic Processes; Artificial Intelligence; Logic; Probability and Statistics in Computer Science